Do the rich vote conservative because they are rich? - Jo Thori Lind (University of Oslo, Department of Economics, 2006)
Political economy models predict that the rich oppose redistribution, and hence vote for conservative parties. Although this seems to fit the data well, I show that this is not true when we control for unobservable characteristics. Using Norwegian survey data, I study to what extent voting is caused by income. Unobserved characteristics correlated with income are handled by using fixed effects panel data discrete choice models. Although a positive association between income and conservative voting persists when controlling for unobservables, the magnitude of the effect is reduced by a factor of five. To correct for measurement error, I instrument income with average income by profession. The magnitude of the coefficients is increased, but the main conclusions remain.
Keywords: C23; C25; D31; D72; H11; H53; 330; Political economy; redistribution; voting; multinomial logit; panel data; Einkommen; Wahlverhalten; Verteilungspolitik; Panel; Norwegen